O panorama dos crimes ambientais ocorridos na comarca de Uruguaiana e processados na justiça federal na segunda década do século XXI - (:unkn) unknown (Universidade Federal do Pampa, 2022)
The theme of this work is the panorama of environmental crimes occurred in the district of Uruguaiana and processed in the Federal Court (TRF4) in second decade of the 21st century, between 2010 and 2021. The general objective is analyze the environmental crimes that occurred in the region of Uruguaiana, verifying where and what crimes were committed, in order to define which environmental crimes most recurrent during the defined period. Therefore, the method used in this research is deductive, starting with the concept of environment and environmental law, passing through the creation of legislation on environmental crimes, until reaching the decisions that occurred most in the region of Uruguaiana in the second decade of the XXI century. From the point of view of technical procedures, bibliographic and documentary research related to the topic in question. At bibliographical approach, books, scientific articles, publications were used, which supported the theoretical-legal basis. In the documentary research, primary sources, such as TRF4 decisions and public documents that regulate the matter. In this way, 55 decisions were found within the scope of the Federal Court of Uruguaiana between 2010 and 2021. According to the research carried out, environmental crimes occurred in around 74.55% of cases in the municipality of Uruguayan. Regarding crimes, 45.45% relate to imports, illegal storage and transport of pesticides and 16.36 illegal fishing on the banks of the Uruguay River. And with regard to the sanctions applied, the majority are penalties restriction of rights and fine, both sanctions are applied in around 27.27% of decisions. Therefore, this research demonstrates that in the years 2010 the 2021, the environmental crimes that occurred most in Uruguaiana are those that involve pesticide trafficking and illegal fishing on the banks of the Uruguay River, which is justified due to the territorial location of the municipality.
The panorama of environmental crimes that occurred in the region of Uruguaiana and prosecuted in federal justice in the second decade of the 21st century
Keywords: Meio ambiente; Crimes ambientais; Direito ambiental; Uruguaiana-RS; Environment; Environmental crimes; Environmental law; CNPQ::CIENCIAS SOCIAIS APLICADAS